Knights, Cooks, Monks and Tourists: Elite and Popular Experience of the Late-Medieval Jerusalem Pilgrimage - Beebe, Kathryne (Studies in church history, 2006)
The Church of the Holy Sepulchre in the late Middle Ages was the centre of a range of pilgrimage activity in which elite and popular beliefs and practices overlapped and complicated each other in exciting ways. The Jerusalem pilgrimage, in the fourteenth and fifteenth centuries in particular, abounded in multiple levels of ‘elite’ and ‘popular’ experience. Through the pilgrimage writings of a fifteenth-century Dominican pilgrim named Felix Fabri, this paper will explore two specific levels: the distinction between noble and lower-class experiences of the Jerusalem pilgrimage (both physical and spiritual), and the distinction between spiritually ‘elite’ and ‘popular’ conceptions of pilgrimage itself - that uneasy balance between the spiritually-sophisticated, contemplative experience of pilgrimage promoted by St Jerome and the more ‘popular’ interest in traditional ‘tourist’ activities, such as gathering indulgences or stocking up on holy souvenirs and relics to take home. However, as we will see, even these tourist acts were grounded in the orthodox spirituality of late-medieval piety, and the elite and popular experiences of pilgrimage, whether social or spiritual, were not so distinct as they may first appear.